Mouse models of chronic lymphocytic leukemia and Richter transformation: what we have learnt and what we are missing - Bertilaccio, Maria Teresa Sabrina; Chen, Shih-Shih (Frontiers in Immunology, 2024)
Although the chronic lymphocytic leukemia (CLL) treatment landscape has changed dramatically, unmet clinical needs are emerging, as CLL in many patients does not respond, becomes resistant to treatment, relapses during treatment, or transforms into Richter. In the majority of cases, transformation evolves the original leukemia clone into a diffuse large B-cell lymphoma (DLBCL). Richter transformation (RT) represents a dreadful clinical challenge with limited therapeutic opportunities and scarce preclinical tools. CLL cells are well known to highly depend on survival signals provided by the tumor microenvironment (TME). These signals enhance the frequency of immunosuppressive cells with protumor function, including regulatory CD4+ T cells and tumor-associated macrophages. T cells, on the other hand, exhibit features of exhaustion and profound functional defects. Overall immune dysfunction and immunosuppression are common features of patients with CLL. The interaction between malignant cells and TME cells can occur during different phases of CLL development and transformation. A better understanding of in vivo CLL and RT biology and the availability of adequate mouse models that faithfully recapitulate the progression of CLL and RT within their microenvironments are “conditio sine qua non” to develop successful therapeutic strategies. In this review, we describe the xenograft and genetic-engineered mouse models of CLL and RT, how they helped to elucidate the pathophysiology of the disease progression and transformation, and how they have been and might be instrumental in developing innovative therapeutic approaches to finally eradicate these malignancies.